Costo y plazo aplicando el método pert en la construcción muro de Contencion en rivera Rio Tandapi, cantón Mejía, Pichincha. - Ordóñez Apolo, Jordy Vicente (My University, 2019)
Introduction, The planning and programming of a civil construction project is very important because it allows us to efficiently distribute the times and costs of the activities to be carried out and we can program the project term at a referential cost. General Objective, to elaborate the cost and term of the retaining wall in Rivera Rio Tandapi of Canton Mejía, of the Province of Pichincha, through the PERT method Project Evaluation and Review Techniques, to minimize the times and costs of the same. Specific Objectives, to plan the civil works of the retaining wall in Rivera Rio Tandapi, develop schedules for physical advancement, and, determine the workforce to be used, materials, machinery and technical help, through tabulations in Excel which will allow us to obtain a better appreciation of results. Materials and methods, we begin with the planning which covers about sixteen different activities, the same ones that will be solved in sequence for the correct arrow diagram, In programming, we obtain the durations table, then the probabilistic times table, and finally by calculating the standard deviation and variance, we find the critical route, ending with schedules corresponding to the material, labor and progress. Conclusion, We have concluded that the reference cost according to the budget is $21.687.80, and, with a term according to schedules of 45 referential days.
Introducción, La planificación y programación de un proyecto de construcción de una obra civil es muy importante porque nos permite distribuir de una forma eficaz los tiempos y costos de las actividades a realizarse y podamos programar el plazo del proyecto a un costo referencial. Objetivo General, elaborar el costo y plazo del muro de contención en Rivera Rio Tandapi del cantón Mejía, de la Provincia del Pichincha, a través del método PERT Project Evaluation and Review Techniques, para minimizar los tiempos y costos del mismo. Objetivos Específicos, planificar la obra civil del muro de contención en Rivera Rio Tandapi, elaborar cronogramas para el avance físico, y, determinar la mano de obra a utilizar, materiales, maquinaria y ayuda técnica, mediante tabulaciones en Excel las cuales nos permitirán obtener una mejor apreciación de resultados. Materiales y métodos, iniciamos con la planificación la cual abarca cerca de dieciséis actividades diversas, las mismas que serán resueltas en secuencia para el correcto diagrama de flechas; en la programación, obtenemos la tabla de duraciones, luego la tabla de tiempos probabilísticos, y por ultimo mediante el cálculo de la desviación estándar y varianza, encontramos la ruta crítica, finalizando con cronogramas respectivos al material, mano de obra y avance. Conclusión, Hemos concluido que el costo referencial acorde al presupuesto es de $21.687.80, y, con un plazo acorde a cronogramas de 45 días referenciales.
Keywords: PLANIFICACION; PROGRAMACION; COSTO; PLAZO